ANALISIS PENGGUNAAN TERTINGGI DAN TERBAIK TANAH KOSONG MILIK PT. PERTANI (PERSERO) (STUDY TANAH DI JALAN AHMAD YANI KELURAHAN DAWUAN KABUPATEN KARAWANG) - , JOHNNY MALELA MARPAUNG, S.T., Wakhid Slamet Ciptono, M.B.A., M.P.M., Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
The highest and best use research for the vacant land owned by PT. Pertani (Persero) at Jalan Ahmad Yani, Dawuan, Kabupaten Karawang, conducted through the analysis process on properties productivity based on the legal and regulatory aspects as well as the physical and location aspects, next step is the analysis of demand and market supply and financial feasibility analysis for each proposed use. The data that will be analyze consists of primary data and secondary data. Primary data include data revenues, rents and expenses proposed as an alternative to the use, obtained by doing a structured interview, while the physical data which include size, land shape, utilities and others obtained through interviews and observation, while the secondary data obtained from Panangian Simanungkalit, Colliers International Indonesia, the Ministry of Finance, Bank Indonesia. From all analysis results obtained, comes two proposed land use which is appropriate and allowed. The highest and best use of the land is for industrial warehousing area and commercial area (shopping area). Based on indicators of financial viability with the Net Present Value (NPV), Internal Rate of Return (IRR), Payback Period (PBP), then the use of industrial warehousing area indicated better than commercial area (home shops area), so it can be concluded that the land use option for industrial warehousing area is the most optimal.